The Modernist Poem or the Infinite Prolegomena - Aurore Clavier (Transatlantica)
Starting from Giorgio Agamben’s observation that “the end of the poem” is threatened by generic indefiniteness, this article explores what occurs when, on the other end, the text refuses to begin, postponing its own formulation in favor of a never-ending foreword. Far from enabling an absolute contact between words and things that would settle once and for all the ambiguous relationship between reality and imagination, the seemingly close unit of the poem or collection, more particularly as it was expressed by American modernism, is thus jeopardized, the text being assigned to the virtuality of a “placeless place” (Aristotle; Agamben) where poetry and philosophy may meet. Refusing its own closure, the page of the poem, through the fluctuations of its contours and the engagements it stages, joins the tentative field of the essay, thereby abolishing generic categories as much as the Platonic scission between philosophical and poetical words.